Support Services for International Graduate Students at Makerere University - Winifred Namuwonge (East African Journal of Education Studies, 2024)
Makerere University is focused on being a research-led university, which necessitates it embrace an internationalisation agenda to fit into the global research network. There is a need to boost the number of international graduate students to help Makerere University realise her vision. This qualitative study explores how international graduate students are supported at Makerere University. The following objective guided it: to explore how international graduate students are supported at Makerere University. The study was anchored in the interpretivism world view, subscribing to the transcendental phenomenology of Edmund Husserl to uncover the support given to international graduate students. Eight international graduate students at Makerere University were interviewed and selected from different academic disciplines categorised according to Becher and Biglan's classification of academic disciplines. Both unstructured interviews and documentary check data generation strategies were used in this study. Data analysis followed a thematic approach whereby various forms of support were provided to international graduate students at Makerere University, and how it is provided was identified. It was concluded that those international graduate students received non-academic and academic support at Makerere University. This study recommends that Makerere University Management provide financial, human, and physical resources to the International Office as ways of facilitating international graduate students to complete their study programs and attracting many more to join the University. The International Office may work with the Office of the Dean of Students to organise events for graduate students to facilitate interactions between international and domestic students, and they may also put in place peer mentors for new international graduate students to foster a sense of community. This study recommends that the International Office work very closely with the schools in the different Colleges of Makerere University, especially establishing a desk officer in each of the Dean's Office to handle issues of international students as this may improve their numbers at Makerere University. Finally, the university management should strengthen and streamline the activities of the International Office at Makerere University